Extranodal extension is a strong prognosticator in HPV‐positive oropharyngeal squamous cell carcinoma. (11th May 2019) - Bauer, Eric; Mazul, Angela; Chernock, Rebecca; Rich, Jason; Jackson, Ryan S.; Paniello, Randal; Pipkorn, Patrik; Oppelt, Peter; Gay, Hiram; Daly, Mackenzie; El‐Mofty, Samir; Thorstad, Wade; et al.
Abstract : Objective: To comprehensively examine the prognostic significance of extranodal extension (ENE) in human papillomavirus–positive oropharyngeal squamous cell carcinoma (HPV‐positive OPSCC). Methods: Retrospective cohort of cases diagnosed with HPV‐positive OPSCC from 2010 to 2015 in the National Cancer Database. Inclusion of all OPSCC HPV‐positive cases with appropriate International Classification of Diseases‐0‐3 codes that received surgery with a neck dissection. Univariate and multivariable analyses were conducted. Hazard ratios (HR) for the independent effects of ENE and N stage on overall survival were estimated by Cox proportional hazards regression. Results: Cases that were ENE‐negative had the highest 5‐year survival (92.6%; 95% confidence interval [CI]: 90.5%–94.7%). ENE‐positive cases had the lowest 5‐year survival (84.0%; 95% CI: 80.7%−87.4%). After adjusting for confounding variables, ENE‐positivity was associated with almost twice the hazard of death (HR = 1.90; 95% CI: 1.35–2.67) compared to ENE‐negative cases. Nodal (N) category 1, ENE‐positive status was associated with an increased risk of death (HR = 1.88; 95% CI: 1.26–2.80) compared with N1, ENE‐negative status. Compared to N1/ENE‐negative cases, N2/ENE‐positive cases had the poorest survival (HR: 2.93; 95% CI: 1.94–4.43). Both microscopic and macroscopic ENE were associated with worse outcomes compared to node‐positive/ENE‐negative status. Conclusion: The implementation of the American Joint Committee on Cancer 8th edition staging system provides a much‐improved framework to develop and discuss treatment plans for HPV‐positive OPSCC. We feel that careful consideration should be given to the importance of ENE in patients with HPV‐positive OPSCC. Level of Evidence: 4 Laryngoscope, 130:939–945, 2020